Occupational exposure to photocopiers and their toners cause genotoxicity. (February 2018) - Kasi, V; Elango, N; Ananth, S; Vembhu, B; Poornima, JG
Photocopier machines are inevitable office equipment, but they are also sources of air pollution. Millions of people across the world are involved in the operation and maintenance of photocopiers. We aimed to evaluate the potential genotoxic effects of exposure to photocopiers in photocopier operators and maintenance personnel by Comet assay. This study involved 50 photocopier operators, 61 maintenance personnel and 52 controls. Both the photocopier exposed groups exhibited significantly increased DNA damage when compared to controls. Cumulative exposure to photocopiers was the most significant contributor for genotoxicity ( p < 0.001). Genotoxicity among photocopier maintenance personnel may be due to the presence of carbon black, iron, silicon, magnetite and the high levels of other elements in the photocopier toners. Genotoxicity among photocopier operators might be due to exposure to high levels of particulate matter and volatile organic compounds emitted by photocopiers during operation. Research is essential to improve toner manufacturing processes and chemical composition of toners to reduce genotoxicity. Clean technologies are the need of the day to cut down on particulate matter and volatile organic compound emissions from photocopiers.